Answer:
1 . x = 9,
2 . n = 4,
3 . Clare made an error in the 2nd step; Correct answer is y = - 65 / 11
Step-by-step explanation:
1 .
[tex]2 * ( x + 5 ) = 3x + 1 - Apply Distributive Property,\\\\2x + 10 = 3x + 1 - Subtract 2x from Either Side,\\10 = x + 1 - Subtract 1 from Either Side,\\\\x = 9,\\Conclusion; x = 9[/tex]
2 .
[tex]3 * ( n + 2 ) = 9 * ( 6 - n ) - Apply Distributive Property,\\\\3n + 6 = 54 - 9n - Add ( 9n ) on Either Side,\\12n + 6 = 54 - Subtract 6 from Either Side,\\\\12n = 48 - Divide Either Side by 12,\\n = 4,\\\\Conclusion; n = 4[/tex]
3 . Clare made an error in the second step ( 72 + 24y = 4y - 5 - 9y ) and to derive the correct solution, see the following steps below;
[tex]12 * ( 5 + 2y ) = 4y - ( 5 - 9y ),\\60 + 24y = 4y - 5 + 9y,\\65 + 24y = 4y + 9y,\\65 + 24y = 13y,\\\\65 = - 11y,\\y = - 65 / 11\\\\Conclusion; y = - 65 / 11[/tex]
Which function is represented by the graph below?
Answer:
y= 2x-4
Step-by-step explanation:
The y-intercept is at -4, it is a positive slope, plotting from the y-axis rise over run is equal to 2/1 which means that the slope is 2x. giving you y= 2x-4
The equation which satisfy to the graph is Y= 2x- 4
What is an equation?An equation is a mathematical expression that contains an equals symbol. Equations often contain algebra.
According to graph
There are multiples points given on which line was passing
But we will select only which is clear
1st point = (0, 2)
2nd point = (-4,0 )
Now we will put values on equations and check which will satisfy
For 1st equation
Y= 2x- 4
Checking with 1st point
Putting x= 2
Y= 0 which satisfy
Checking for 2nd point
Putting x=0
Y = -4 satisfy
Hence, equation which satisfy to graph is Y= 2x- 4
To know more about equation here :
https://brainly.com/question/24169758
# SPJ2
Soledad has a storage box. The box is 6 1/2 inches long, 4 3/4 inches wide and 7 inches tall. She wants to run a border around the top of the box. How much border does she need?
Answer:
She need 10.5 inches border
Step-by-step explanation:
Length of box =[tex]\frac{1}{2} inches[/tex]
Breadth of box =[tex]4\frac{3}{4} inches[/tex]
Breadth of box =[tex]\frac{19}{4} inches[/tex]
Height of box = 7 inches
Now we are given that Soledad wants to run a border around the top of the box.
So, Length of top = Perimeter = [tex]2(l+b)=2(\frac{1}{2}+\frac{19}{4})=10.5[/tex]
Hence She need 10.5 inches border
14. Roger is on a playground swing, and he is swinging back and forth in such a way that the height, h, in feet, of the swing off the ground is given by the equation h=3cos(3π/2t) +5, where t is in seconds. How many seconds elapses between two consecutive times that the swing is at its maximum height?
Answer:
The time [tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
Step-by-step explanation:
Explanation:-
Step(i):-
Given function [tex]h(t) = 3 cos (\frac{3\pi }{2 t} ) +5[/tex] ....(i)
By using derivative formulas
[tex]\frac{d cosx }{d x} = -sinx[/tex]
[tex]\frac{d x^{n} }{d x} = n x^{n-1}[/tex]
[tex]\frac{d t^{-1} }{d x} = -1 t^{-1-1} = - t^{-2} = \frac{-1}{t^{2} }[/tex]
Step(ii):-
Differentiating equation(i) with respective to 't'
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})\frac{d}{dt} (\frac{3\pi }{2t } )+0[/tex] ...(ii)
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )+0[/tex]
Equating zero
[tex]h^{l} (t) = 3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )=0[/tex]
[tex]3(-sin(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } ) = 0[/tex]
on simplification , we get
[tex](sin(\frac{3\pi }{2t}) = 0[/tex]
now we use formulas
sin 0 = 0 and sinπ = 0
General solution
[tex](sin(\frac{3\pi }{2t}) = sin\pi[/tex]
[tex](\frac{3\pi }{2t}) = \pi[/tex]
Cancellation 'π' on both sides, we get
[tex]3 = 2 t[/tex]
Dividing '2' on both sides , we get
[tex]t = \frac{3}{2}[/tex]
Again differentiating with respective to 't' , we get
[tex]h^{ll} (t) = 3(-cos(\frac{3\pi }{2t})(\frac{-3\pi }{2t^{2} } )+ (-3)(-sin(\frac{3\pi }{2t} )(\frac{6\pi }{2t^{3} }[/tex]
Put t= 3/2 and simplification
[tex]h^{ll} (t) < 0[/tex]
The maximum height
[tex]h(t) = 3 cos (\frac{3\pi }{2 t} ) +5[/tex]
[tex]h(\frac{3}{2} ) = 3 cos (\frac{3\pi }{2(\frac{3}{2} )} )+5[/tex]
[tex]h(\frac{3}{2} ) = 3 cos (\pi )+5 = -3+5 =2[/tex]
[tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
Conclusion:-
The time [tex]t = \frac{3}{2}[/tex] seconds elapses between two consecutive times that the swing is at its maximum height 'h' = 2
evaluate the following expression -7x(7+9)
Answer:
-112
Step-by-step explanation:
Add
-7(7+9)
Multiply
-7x16
Wallah! You have the answer
-112
[tex]\text{Simplify the expression:}\\\\-7x(7+9)\\\\\text{Use the distributive property}\\\\-49x-63x\\\\\text{Combine like terms}\\\\\boxed{-112x}[/tex]
A new car is purchased for 23400 dollars. The value of the car depreciates at 11.5% per year. To the nearest year, how long will it be until the value of the car is 12700 dollars?
Answer: 5 years
Step-by-step explanation:
Using same formula as for Compound Interest:
12700 = 23400 (1-.115)^t
12700 = 23400 x 0.885^t
0.885^t = 127/234
Convert decimal into fraction:
177/200^t = 127/234
Take logarithm of both sides of thr equation:
t = log 177/200 (127/234)
t = 5.00242
I need help with is question ASAP please
The y-intercept looks like it's 0 and the slop looks like 6/2 or 3 or maybe 7/2
what is the surface area of a rectangle 4/3 x 5/4 x 2/3
Answer:
surface area of rectangle= 2[(l+w) +(l+h). +(w+h)]
hope it helps
Yumi and Juan pick up litter along the highway at the same rate. Yumi picks up litter for 3 miles and takes 2 hours
longer than Juan, who picks up litter for 2 miles. If Juan spent x hours picking up litter, the following equation models
the situation
XX+2
How long did Yumi spend picking up litter?
1 hour 20 minutes
O 3 hours 20 minutes
4 hours
6 hours
its 6 hours
Answer:
6 hours
Step-by-step explanation:
Let's say that the number of hours that Yumi picked litter for is y.
You know that since Yumi picked litter for 2 hours more than Juan, y=x+2.
y=3m
x=2m
Subtract the second equation from the first:
y-x=m
Substitute:
x+2-x=m
2=m
This means that it takes 2 hours per mile of litter. Multiplying this by the 3 miles that Yumi walked makes a total of 6 hours. Hope this helps!
Answer:
D. 6 hours
Step-by-step explanation:
PLEASE HELP WILL GIVE BRAINLIEST AND 20 POINTS
solve this system of equations
3y-5x=12
y=1/3x
Answer:
x=-3
y=-1
(-3,-1)
Answer:
(-3, -1).
Step-by-step explanation:
I have attached the work to your problem.
Please see the attachment below.
I hope this helps!
help me need it now asap
Answer:
Number of half units =10; V= 1 1/4
Step-by-step explanation:
1*5/4*1/2=5/4 = 1 1/4
A. 256
B. 265
C. 297
D. 279
Answer:
A.
Step-by-step explanation:
So calculate one of the triangles.
[tex]\frac{12*8}{2} =48[/tex]
48 * 4 = 192
192 + 64 = 256
The area of the base of the cone is 64π square millimeters, and the area of the lateral surface is 112π square millimeters. Find the radius r and slant height ℓ of the cone.
Answer:
Radius = 8 mm
Slant Height = 14 mm
Step-by-step explanation:
Base of a cone is a circle.
Area of circle is given as [tex]A=\pi r^{2}[/tex]
Where [tex]r[/tex] is the radius.
Given that
[tex]A = 64 \pi\ mm^2\\\Rightarrow \pi r^{2} = 64\pi \\\Rightarrow r^{2} = 64\\\Rightarrow r = 8\ mm[/tex]
Hence, radius is 8 mm.
Formula for Lateral Surface Area of a cone:
[tex]LSA = \pi rl[/tex]
Where [tex]r[/tex] is the radius and
[tex]l[/tex] is the slant height of cone
Given that [tex]LSA = 112 \pi\ mm^2[/tex]
[tex]\Rightarrow 112\pi = \pi \times 8 \times l\\\Rightarrow 8 \times l = 112\\\Rightarrow l = 14\ mm[/tex]
Hence, slant height is 14 mm
Which transformations are nonrigid transformations? Select two options. dilation reflection rotation stretch translation
Nonrigid transformations are transformations that change the side lengths or angles of a shape
The nonrigid transformations are dilation and stretch
All type of transformations are rigid transformation, except dilation.
The dilation transformation is divided into two types
StretchCompressHence, the nonrigid transformations are dilation and stretch
Read more about transformations at:
https://brainly.com/question/4289712
Answer:
A and D
Step-by-step explanation:
Which is a factor of x^2-9x + 18?
Answer:
(x-6)
Step-by-step explanation:
The factor form of that trinomial is: (x-3)(x-6), so the second option listed (x-6) is the one to select
Answer:
X-6=0
Step-by-step explanation:
Because the factors are 6 and 3
Match the building block of geometry to the statement that defines it.
postulate
a visual tool representing mathematical
ideas to be interpreted
theorem
a mathematical statement proven using
postulates and definitions
definition
a mathematical statement taken as fact
diagram
a formal statement declaring the meaning of
a word
Answer:
c: a mathematical statement taken as fact diagram
Step-by-step explanation:
a mathematical statement taken as fact
diagram
This can mean what we mean when 'we say what the word means when compared to what it means when we are to use reason meaning the same word as reasoning it shows us the fatcs in an efficient way'
Postulate means reasoning in mathematics.
Postulate → Option 3
Theorem → Option 2
Definition → Option 4
Diagram → Option 1
How to arrange the blocks ?Postulate : Postulate is a mathematical statement that is taken to be true without any proof, i.e. "A mathematical statement taken as fact".
Theorem : Theorem is a statement that can be proved using some logical arguments, facts and definitions, i.e. "A mathematical statement proven using postulates and definitions".
Definition : Definition is used to describe the meaning of something, i.e. "A formal statement declaring the meaning of a word".
Diagram : Diagram is a figure which consists of various structures as per our need, i.e. "A visual tool representing mathematical ideas to be interpreted".
Learn more about Postulate, theorem, definition and diagram here :
https://brainly.com/question/16843335
#SPJ2
Which expression is a sum of cubes?
O-27ab6 +8a9b12
-9a3b6 +8810
O 9a3b6 +8a9b12
27a368 + 8a612
Answer:
[tex]-27 a^3 b^6 + 8 a^9 b^{12} [/tex]
Step-by-step explanation:
In the picture attached, the problem is shown.
A polynomial in the form x³ + y³ is called a sum of cubes
If we take the expression:
[tex]-27 a^3 b^6 + 8 a^9 b^{12} [/tex]
and take cubic root to each term, we get:
[tex] x = \sqrt[3]{-27 a^3 b^6} [/tex]
[tex] x =\sqrt[3]{-27} \sqrt[3]{a^3} \sqrt[3]{b^6}[/tex]
[tex] x = -3 a b^2[/tex]
[tex]y = \sqrt[3]{8 a^9 b^{12}} [/tex]
[tex] y =\sqrt[3]{8} \sqrt[3]{a^9} \sqrt[3]{b^{12}}[/tex]
[tex] y =2 a^3 b^4[/tex]
The other options are not sum of cubes because 9, -9, b^10 and b^8 are not a perfect cubes.
Helppppp meeeee answer thissssssss
Answer:
(-1.025)^3 x (-1.025)^2=(- 1.025)^5
(-y)^3 x (-y)^2 x (-y)= y^6
5= odd, - stays
6= even, - becomes +
Answer:
5) (-1.025)^3* (-1.025)^2 = (-1.025)^5 = (-41/40)^5
10) -y^3 * -y^2 * -y
Multiplying an odd number of negative terms makes the product negative
= - y^3 * y^2 * y
= - y^6
Which of the following does the number line represent?
Answer:
1 or the first option going down
Step-by-step explanation:
Answer:
1st one
Step-by-step explanation:
your start point is negative three (not positive three) then usually a tip is when ur variable is first in the equation the sign will tell you which way the arrow will go
How many different 5-digit numbers can be formed with the digits 3,4,5,6, and 7, if each digit is used only once ?
Answer:
it should be either option 1 or option 3
Step-by-step explanation:
Solve:
-3(7p + 5) = 27
Helpppp
Answer:
-2
Step-by-step explanation:
-21p - 15 = 27
-21p = 42
p = -2
Answer:
-2
Step-by-step explanation:
-21p - 15 = 27
-21p = 42
p = -2
plz help i will give brainliest!!! 2.5(4x+10)−2(3x−15)
Answer:
4x+55
Step-by-step explanation:
Expand and simplify
10x+25x-6x+30
4x+55
Answer:
4x+55
Step-by-step explanation:
I used the PEDMAS to simplify the equation doing the parentheses first then addition and subtraction. The picture attached showed what order I did it in and I hope this really helped! Good LUCK on the rest of your homework.
A soccer ball is kicked toward the goal. The height of the ball is modeled by the function h(t) = −16t2 + 48t where t equals the time in seconds and h(t) represents the height of the ball at time t seconds. What is the axis of symmetry, and what does it represent?
Answer:
The Axis of symmetry shows the highest point on the line and is a vertical line at the highest point on the graph x=1.5, y=36
Step-by-step explanation:
checked on a graphing calculator
Answer:
t = 1.5; it takes 1.5 seconds to reach the maximum height and 3 seconds to fall back to the ground.
Step-by-step explanation:
Arrange from smallest to largest
0.01, 1.01, 10.01, 1.001
Answer:
0.01 --> 1.001 ---> 1.01 ---> 10.01
The numbers in the ascending order:
0.01, 1.01, 1.001, 10.01.
What is ascending order?Putting numbers in ascending order simply means to do it from smallest to largest.
Given:
0.01, 1.01, 10.01, 1.001.
The numbers from smallest to largest:
That means, in the ascending order.
So,
0.01, 1.01, 1.001, 10.01.
Therefore, 0.01, 1.01, 1.001, 10.01 are in the required order.
To learn more about the ascending order;
https://brainly.com/question/20681445
#SPJ2
soooo i need help can yall find the answer for me I put mad points so better get it right .
Answer:
1.08 * 10 ^8
Step-by-step explanation:
2.4 * 10^4 * 4.5 * 10^3
Multiply the constants
10.8
Add the exponents
10^(4+3) = 10^7
Put together
10.8 * 10 ^7
Put we can only have one number in front of the decimal
Move the decimal one place to the left and add one to the exponent
1.08 * 10 ^8
What is the midpoint of the segment below? (2,3)(-3,-2)
Answer:
(-0.5, 0.5)
Step-by-step explanation:
If those two points are endpoints, just use the midpoint formula.
(-0.5, 0.5)
Answer:
(-1/2,1/2)
Step-by-step explanation:
To find the midpoint, add the x coordinates and divide by 2
(2+-3)/2 = -1/2
add the y coordinates and divide by 2
(3+-2)/2 = 1/2
The midpoint is (-1/2,1/2)
What is -6 divided by -1.2?
Answer:
5.
Step-by-step explanation:
This is the same as saying:
-6/(-6/5).
To solve the equation, we multiply by the reciprocal and simplify. In this case, we multiply both sides of the equation by -5/6.
-6 * (-5/6) = 5.
The answer must be positive, as two negatives divided equal a positive.
I hope this helps!
The solution of expression after divide is,
⇒ 5
We have to given that;
⇒ - 6 is divided by - 1.2
Now, We can simplify as,
⇒ - 6 is divided by - 1.2
It can be written as,
⇒ - 6 ÷ - 1.2
⇒ - 6 / - 1.2
⇒ 6 / 1.2
⇒ 60 / 12
⇒ 5
Thus, The solution of expression after divide is,
⇒ 5
Learn more about the divide visit:
https://brainly.com/question/28119824
#SPJ6
pwease answer UwU ^~w~^
Answer:
I Believe The Answer To Be 21
Step-by-step explanation:
BO is 7 Making O to X 7, AC is 20 Making OC less than 27 more than 20.
Answer:
The answer 21
Step-by-step explanation:
4 of 10
EER
Jeremy wants to buy a new computer
The saleswoman says that he can make a
down payment and then pay for the
computer in installments.
Rewrite the formula to solve for the total price
of the computer.
Enter the correct answer
000
Here's a formula for this scenario:
DON
DOO
X-t-yz
X = amount down
y = money each month
z = number of months
t = total price
Answer:
foodgnfnfnfd2vefvf3vedvwf wsvwsv
[tex]( {2}^{ - 1} + {3}^{ - 1} )^{2} [/tex]
solve.
will give the brainliest
Answer:
25/36
Step-by-step explanation:
(2^-1 + 3^-1)^2
➡
➡
(1/2 + 1/3)^2
➡
(5/6)^2 = 25/36
PLEASE HELP ASAP, hdhehdhdhbd
Answer:
x=11
Step-by-step explanation:
5x+9=6x-2 (corresponding angles)
x=11